2015
DOI: 10.1177/0954411915585380
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of sliding distance and contact mechanics of hip implant under dynamic walking conditions

Abstract: This is a repository copy of Finite element analysis of sliding distance and contact mechanics of hip implant under dynamic walking conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 22 publications
5
22
0
Order By: Relevance
“…Given the lack of studies based on comprehensive patient‐specific data in the current literature, we compared our results qualitatively with previous reports that included single set of kinematics. The accumulation of sliding distance during gait cycle in our study agrees well with earlier findings, as shown in Figure b. All plots exhibited a sharp increase around 60% gait cycle, possibly because of a high transient high flexion velocity at toe‐off.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Given the lack of studies based on comprehensive patient‐specific data in the current literature, we compared our results qualitatively with previous reports that included single set of kinematics. The accumulation of sliding distance during gait cycle in our study agrees well with earlier findings, as shown in Figure b. All plots exhibited a sharp increase around 60% gait cycle, possibly because of a high transient high flexion velocity at toe‐off.…”
Section: Discussionsupporting
confidence: 92%
“…Wear of ultra‐high molecular weight polyethylene (UHMWPE) is closely related to the relative motion of the articulating surfaces. Owing to the convenience in implementing the material wear law, computational modeling has been frequently employed as a useful tool to investigate the wear behavior of UHMWPE . In the pioneering work by Maxian et al the calculation of sliding distance was incorporated into their finite element model and the Archard wear law was implemented to predict wear rate.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Intel® Core(TM) i7-6820HQ CPU). However, Gao et al reported a total computational time for just solving motion equations of about 4 and 5 hours for implicit and explicit finite element simulations, respectively, on a 3.5 GHz personal computer [81]. Therefore, the developed model can be used to perform parametric studies for optimizing and assessing new implant designs due to relatively low computational time.…”
Section: Resultsmentioning
confidence: 99%